What are we talking about when we refer to humane entrepreneurship? - Santos, Juliana Moreira dos; Machado, Hilka Pelizza Vier; Pereira, Gabriela Santos; Santos, Susana C. (REGEPE Entrepreneurship and Small Business Journal, 2026)
Purpose: To examine the foundations that underpin the concept of Humane Entrepreneurship (HumEnt) and to present the evolution of studies in this field. Problem: Humane entrepreneurship is a novel concept within the field of entrepreneurship, and distinct approaches have discussed the phenomenon, often obscuring its understanding. Method: A systematic literature review guided by the PRISMA protocol, using Rayyan software for study screening and Bibliometrix and VOSviewer for systematic and bibliometric analyses of 32 articles selected from the Web of Science, Scopus, Emerald Insight, and ScienceDirect databases. Main results: The data show that HumEnt does not have clearly defined boundaries but indicates its evolution and related topics such as entrepreneurial education, ecosystems, social, community, and creative entrepreneurship, in addition to critiques of the model. Issues such as religion and digitalization were also discussed in the context of HumEnt. Theoretical contributions: We present an integrated and systematized view of HumEnt, contributing to the definition of its scope and applicability in different contexts, facilitating its recognition and expansion. We also propose an agenda for future research, encouraging ongoing academic debate and exploration of new dimensions of HumEnt. Relevance/Originality: HumEnt is an emerging concept that provides an opportunity to examine humane entrepreneurial practices. Social/management contributions: The study may encourage entrepreneurs to adopt management styles that focus on human, social, and environmental capital, and to promote governmental actions to foster entrepreneurship aligned with the Sustainable Development Goals. For Brazil and other Global South countries, the practice of HumEnt can leverage human capital and promote economic and social development in these regions.